The development and evaluation of a flat-type wooden incubator (1998)
"A flat-type, 60-egg capacity incubator was designed, constructed and tested. The incubator differs from existing designs in that the cabinet was made from a 3-ply, 4mm thick interior grade plywood to reduce cost and at the same time enhance heat insulation. Also, two domestic kerosene lanterns were provided to supplement heat generation by three 40 W electric bulbs during electricity outages as commonly experienced in Nigeria.When tested with 30 eggs of a commonly sold chicken breed, incubated at average temperature of 38° C and relatively humidity of 58%, the chicks were hatched within 20 days. Relatively high percentages of fertility and hatchability of 86.2% and 76% respectively, as well as a relatively low chick mortality rate of 18.5% were recorded. "